Qualitative analysis of connective tissue stroma in different grades of oral squamous cell carcinoma: A histochemical study - Smitha Kullage; Maji Jose; Vagish Kumar L Shanbhag; Riaz Abdulla (Wolters Kluwer Medknow Publications, 2017)
Background: Detection of oral cancer at an early stage is of utmost importance to decrease morbidity and mortality. Tumor stroma plays a critical role during carcinogenesis. There is lack of information regarding the characteristics of the stroma in relation to the invading malignant epithelial cells and the interdependence between stroma and tumor cells in different grades of oral squamous cell carcinoma (OSCC). Aim: The present study was aimed to analyze and compare the nature of stroma in the vicinity of invading tumor islands in different grades of OSCC, using a histochemical technique picrosirius-polarization method. The present study also evaluated and correlated the possible role of inflammatory response in determining the nature of the stroma. Subjects and Methods: The study included thirty cases of different grades of histologically diagnosed OSCC and ten sections of normal buccal mucosa as a control group. Nature of collagen was analyzed using picrosirius-polarization method, and intensity of inflammatory cell infiltrate was recorded using ImageJ software (1.42q, NIH, USA). The results were tabulated and analyzed statistically. Results: Normal oral mucosa showed predominantly reddish birefringence. All cases of well-differentiated OSCC showed reddish-orange color. Nearly 70% moderately differentiated cases showed yellowish-orange (YO) and 60% of poorly differentiated cases, showed greenish-yellow (GY). The mean inflammatory cell count was highest in well-differentiated group. There was shift to YO and GY collagen when the cell differentiation and inflammatory cell count decreased in moderate and poorly differentiated cases. Conclusion: Both inflammatory cells and tumor cells have a role in determining the nature of the collagen fibers in tumor stroma of OSCC, probably with opposing effects on stromal behavior and hence both are significant in predicting prognosis.